MURSYID ATAU MEMURSYIDKAN: EXPLORASI FENOMENOLOGIS PADA AJARAN TQN PONDOK PESANTREN SURYALAYA - Abas, Abdul (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research aims to find out the genealogy and existence of the Mursyid Guru in the Thariqat Qadiriyah Naqsyabandiyah (TQN) at the Suryalaya Islamic Boarding School. This research uses the library research method, namely by examining and analyzing various relevant literature sources, such as books, scientific journals, manuscripts, official documents, and written works that discuss TQN and spiritual leadership (kemursyidan) at the Suryalaya Islamic Boarding School. Data analysis is carried out in a descriptive-qualitative manner through a content analysis approach to reveal the patterns, meanings, and understandings contained in the text. Data is analyzed through three stages, namely data reduction, data display, and conclusion drawn. The results of the study show that the transfer of the title of chastity in TQN Pontren Suryalaya is not biological hereditary as in the system of inheritance of power, but based on spiritual qualities and certain characteristics that a person must have. Therefore, not every individual can be appointed as a mursyid. An in-depth understanding of the criteria and process for appointing mursyid is an important aspect in the preservation and practice of the teachings of TQN Pontren Suryalaya, although in the current era there are many mursyid claims that are not in accordance with these principles. The contribution of this research is to provide a deeper conceptual understanding of the spiritual leadership system in TQN Pontren Suryalaya. This research can also be an important reference for academics, practitioners of the tariqat, and the general public in distinguishing between spiritually valid murshid and unfounded murshid claims.